2021
DOI: 10.1111/ijsa.12365
|View full text |Cite
|
Sign up to set email alerts
|

The role of fear of negative evaluation in interview anxiety and social‐evaluative workplace anxiety

Abstract: We investigated the consequences of interview and social-evaluative workplace anxiety on job performance, and whether these two anxieties share a common antecedent-fear of negative evaluation. Job applicants (n = 128) completed a survey following their interview and halfway through their work term; supervisory performance ratings were collected at the end of the work term. Fear of negative evaluation was positively correlated with both interview anxiety and social-evaluative workplace anxiety. The correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
(77 reference statements)
1
7
0
Order By: Relevance
“…Consequently, at least one mechanism underlying the negative relation between interview anxiety and interview performance ratings is interviewers’ perceptions of interviewees’ nonverbal behavior. These results, combined with past studies that found that interview anxiety is not related to job performance (Schneider et al, 2019; Zhang et al, 2021), suggest that interview anxiety may be a source of error in interview performance ratings.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Consequently, at least one mechanism underlying the negative relation between interview anxiety and interview performance ratings is interviewers’ perceptions of interviewees’ nonverbal behavior. These results, combined with past studies that found that interview anxiety is not related to job performance (Schneider et al, 2019; Zhang et al, 2021), suggest that interview anxiety may be a source of error in interview performance ratings.…”
Section: Discussionsupporting
confidence: 61%
“…Notably, interview anxiety is not predictive of later job performance (Schneider et al, 2019;Zhang et al, 2021), which suggests that a highly anxious interviewee may receive a low interview rating, despite having the potential to be a good performer if hired. Consequently, interview anxiety is problematic not only for individuals but also for organizations who pass on qualifiedyet anxiousinterviewees, in favor of less suitable ones.…”
mentioning
confidence: 98%
“…So, people who are very sensitive to the fear of being judged negatively are often more likely to be nervous in public interactions where they might be judged by others, like the intention to resume hotel consumption. Zhang et al (2022) looked at how the fear of getting a bad review affects interview anxiety and social-evaluative work anxiety.…”
Section: Underpinning Theoriesmentioning
confidence: 99%
“…Indeed, the social pressure related to a live interaction with another person, especially one that would be in a position to judge the applicant's performance, can trigger social anxiety. These social‐evaluative concerns are particularly salient in a selection context, and indeed fear of negative evaluation is correlated with interview anxiety (Zhang, Powell, & Bonaccio, 2022).…”
Section: Theorizing About Applicants With Disabilities’ Reactions To ...mentioning
confidence: 99%